2022
DOI: 10.1186/s12891-022-05075-5
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment, complications, reoperations, and healthcare costs among patients with clavicle fracture in England

Abstract: Introduction The clinical and economic burden of clavicle fractures in England is not well documented. This study evaluated rates of surgical treatment, post-surgical complications, reoperations and costs in patients with clavicle fractures using the Clinical Practice Research Datalink (CPRD) database. Methods CPRD data were linked to National Health Service Hospital Episode Statistics data. Patients with a diagnosis of clavicle fracture between 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Eighteen (2.9%) of these patients were from our hospital, and ten (1.5%) were referred from other hospitals with an infection. The prevalence of infection is in line with a study by Wolf et al who observed an infection rate of 3.1% (21/672) [16], but higher than the 0.4% (1/251) observed by Shen et al [17]. However, neither of these studies used a validated definition to define infection.…”
Section: Tablesupporting
confidence: 89%
See 1 more Smart Citation
“…Eighteen (2.9%) of these patients were from our hospital, and ten (1.5%) were referred from other hospitals with an infection. The prevalence of infection is in line with a study by Wolf et al who observed an infection rate of 3.1% (21/672) [16], but higher than the 0.4% (1/251) observed by Shen et al [17]. However, neither of these studies used a validated definition to define infection.…”
Section: Tablesupporting
confidence: 89%
“…Studies showed that it has a major impact on the patient's quality of life [12] and can increase hospital-related healthcare costs by up to eight times compared to non-infected fractures [13]. Although studies focusing on infection after operatively treated displaced midshaft clavicular fractures are scarce, infection rates ranging between 0.4% and 7.8% have been reported [14][15][16][17]. As scientific data related to the management of FRI after the operative treatment of clavicular fractures is limited, standardized treatment protocols are almost nonexistent.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies reporting higher nonunion rates after nonoperative treatment and an allegedly better clinical outcome after operative treatment, have led to a shift from nonoperative to operative treatment in the last 15–20 years [ 12 , 13 , 14 ]. Surgically treated patients, however, end up having to undergo second surgery for device removal procedures in more than 85% of cases [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The higher rate of implant removal in women may support this hypothesis. The prebending method proposed by the authors may reduce skin irritation from the plates and patient discomfort, potentially reducing the need for implant removal surgeries [8].…”
mentioning
confidence: 99%